2018
DOI: 10.1002/smi.2840
|View full text |Cite
|
Sign up to set email alerts
|

Stress and sleep remain significant predictors of health after controlling for negative affect

Abstract: Prior research has shown that the predictive power of a stress–health model can be improved by the addition of sleep as a predictor variable. However, negative affect (NA) may act as a confounding variable in stress–health relationships: a source of bias that potentially inflates the observed relationship between stress and health. The current study examines whether stress and sleep remain significant predictors of health after controlling for trait NA. An online survey containing well‐established measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
(97 reference statements)
2
20
0
2
Order By: Relevance
“…Another important indicator of a person's overall health is sleep, since many studies have found positive relationships between sleep and health (Benham & Charak, 2019;Fernandez-Mendoza et al, 2020).…”
Section: Worrying About Covid-19 and Its Effects On Well-being And Sleepmentioning
confidence: 99%
“…Another important indicator of a person's overall health is sleep, since many studies have found positive relationships between sleep and health (Benham & Charak, 2019;Fernandez-Mendoza et al, 2020).…”
Section: Worrying About Covid-19 and Its Effects On Well-being And Sleepmentioning
confidence: 99%
“…It has been shown that stress levels correlate with health. 5,[21][22][23] We also see a similar support for collegiate athletes when athletic programs provide meals or snack bars for athletes. Similarly, the need for employment might also reflect the negative impact of SDH in patients' lives.…”
Section: Value Of Social Determinants Of Health In Athletic Training mentioning
confidence: 74%
“…A vizsgálat eredményei szerint stressz-egészség modellek javíthatók az alvás minőségének változtatásával. Ám tervezik, hogy kifejlesztenek olyan beavatkozásokat, amellyel az alvás által javítható lesz az egészség (BENHAM, 2019). Lászikné (2018) kutatásának célja, hogy megvizsgálja a rendszeresen sportoló nők egészségmagatartását, mentális és fizikai állapotát, továbbá a pszichoszomatikus tüneteket előidéző élethelyzeteit és az azokra való reagálási módjait.…”
Section: Eredményekunclassified